The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1075/itl.18034.rod
|View full text |Cite
|
Sign up to set email alerts
|

Incidental vocabulary learning through viewing television

Abstract: Previous research investigating L2 incidental vocabulary learning from video has primarily focused on short videos from genres that may be conducive to vocabulary learning. The research provides evidence that L2 incidental vocabulary learning can occur through video. However, it is uncertain whether viewing episodes of full-length television programs can contribute to incidental learning. This study investigated the effects of viewing 7+ hours of television on incidental vocabulary learning as well as the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
92
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(116 citation statements)
references
References 50 publications
8
92
2
4
Order By: Relevance
“…Puimège and Peters () demonstrated that learners can also learn the form of unfamiliar lexical items (i.e., single words as well as formulaic sequences) through TV viewing. Looking at extensive TV viewing (i.e., watching 10 full‐length episodes from one TV show), Rodgers and Webb () found that adult EFL learners learned six new words on average and that the learning gains were comparable to those found in reading studies. However, the control group also learned five new words.…”
Section: Vocabulary Learning From Audiovisual Inputmentioning
confidence: 99%
See 4 more Smart Citations
“…Puimège and Peters () demonstrated that learners can also learn the form of unfamiliar lexical items (i.e., single words as well as formulaic sequences) through TV viewing. Looking at extensive TV viewing (i.e., watching 10 full‐length episodes from one TV show), Rodgers and Webb () found that adult EFL learners learned six new words on average and that the learning gains were comparable to those found in reading studies. However, the control group also learned five new words.…”
Section: Vocabulary Learning From Audiovisual Inputmentioning
confidence: 99%
“…Researchers have also addressed the role of a number of word‐related variables in vocabulary learning through TV viewing. Frequency of occurrence has been found to affect word learning positively (Peters & Webb, ), although its effect seems to be smaller in longitudinal studies that investigated extensive viewing (Rodgers & Webb, ). In a recent study, Puimège and Peters () found that a word’s corpus frequency was positively correlated to word learning at the level of form recall.…”
Section: Factors Affecting Vocabulary Learning From Audiovisual Inputmentioning
confidence: 99%
See 3 more Smart Citations